2022
DOI: 10.1088/1361-6439/ac9d46
|View full text |Cite
|
Sign up to set email alerts
|

The effect of quaternary ammonium salts with different chain lengths on copper filling behavior in blind holes of printed circuit board

Abstract: The rapid and defect free blind hole copper super filling is the key technology to ensure the quality and development of printed circuit boards (PCBs). The linear quaternary ammonium compounds with a low molecular weight are expected to act as a potential suppressor for blind hole copper filling. Here, three quaternary ammonium salts with different molecular chain lengths (the dodecyl trimethyl ammonium chloride, the cetyl trimethyl ammonium chloride and the stearyl trimethyl ammonium chloride) were selected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Several research groups have started to purposefully design various oligomer levelers to investigate their structure–property relationships in THs filling. Quaternary ammonium salts have been systematically studied because of their excellent via filling properties [ 25 , 26 ]. Broekmann used polymerizates of imidazole and epichlorohydrin (IMEP) as a model leveler to study the oscillatory behavior during electrodeposition and concluded that the leveling effect originates from the coordination between Cu(I) and the leveler, in which the hydroxyl functional group coordinates Cu(I) to form the IMEP−Cu(I)−MPS complex, inhibiting the activity of MPS [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have started to purposefully design various oligomer levelers to investigate their structure–property relationships in THs filling. Quaternary ammonium salts have been systematically studied because of their excellent via filling properties [ 25 , 26 ]. Broekmann used polymerizates of imidazole and epichlorohydrin (IMEP) as a model leveler to study the oscillatory behavior during electrodeposition and concluded that the leveling effect originates from the coordination between Cu(I) and the leveler, in which the hydroxyl functional group coordinates Cu(I) to form the IMEP−Cu(I)−MPS complex, inhibiting the activity of MPS [ 27 ].…”
Section: Introductionmentioning
confidence: 99%